Psychosocial oncology care resources in Europe: a study under the European Partnership for Action Against Cancer (EPAAC). Issue 4 (21st December 2015) - Travado, Luzia; Reis, Joaquim C.; Watson, Maggie; Borràs, Josep
Abstract: Background: Cancer is a complex health problem requiring multidisciplinary care. There are clinical guidelines available in order to improve the process and outcomes of cancer care within Europe. However, strategic action is still needed in many European Union (EU) Member States to develop or improve national cancer control plans (NCCPs), which play a key role in cancer control and care. The current study clarifies the extent of implementation of psychosocial oncology care (PSOC) in the EU. Method: A survey methodology was used to cover four dimensions: (1) inclusion of PSOC in NCCPs; (2) structure and resources of PSOC delivery; (3) use of NCCP clinical guidelines; and (4) education and training resources available along with determination of training needs in PSOC. Results: Twenty‐seven (90%) countries returned questionnaires of which 21 (78%) include PSOC in their NCCP. However, only 10 (37%) reported having specific budgets for PSOC, 8 (30%) having nationally recommended PSOC clinical guidelines, and 6 countries (22%) reported having an official certification for PSOC education. Conclusion: Although many countries seem to have integrated PSOC into their NCCP, there is still much to do in terms of allocating resources and delivering psychosocial care equitably. Also, there is a need for improving training and certification in PSOC. The findings indicate the need to develop national policies concerning PSOC with clear targets for deliverables in an appropriate timetable in order that psychosocial services and existing clinical guidelines are implemented and fully integrated into EU NCCPs. Copyright © 2015 John Wiley & Sons, Ltd.